Three Level Inverter Based Shunt Active Power Filter Using Multi-Level Hysteresis Band Current Controller - Ucar, Ferhat; Coteli, Resul; Dandil, Besir (Wydawnictwo Sigma-N O T Sp Z O O, 2012)
In this paper, a three-level inverter based Shunt Active Power Filter (SAPF) using Multi-Level Hysteresis Current Controller (MLHCC) is presented for solution of power quality problems in distribution system. A simulation model of SAPF is prepared in Matlab/Simulink environment. MLHCC is used for control of SAPF currents. In simulation study, it is considered that SAPF executes two tasks covering compensation of harmonics and reactive power. Therefore, control algorithm is formed to execute two tasks. The Synchronous Reference Frame Method (SRFM) is used to extract the reference currents. Dynamic performance of SAPF is evaluated using two nonlinear loads switched at different times. Some simulation results are given to show performance of a three-level inverter based SAPF using MLHCC. Simulation results show that current harmonics has been kept inside specific recommendation of IEEE-519 and ac grid is approximately kept in unity power factor.
Keywords: active power filters; three-level h-bridge inverter; multilevel hysteresis band current control; harmonics and reactive power compensation